Ruth Bader Ginsburg, I know this to be true : on equality, determination & service - Ginsburg, Ruth Bader; Blackwell, Geoff (San Francisco, Calif. : Chronicle Books, 2020)
The I Know This to Be True series is a collection of extraordinary figures from diverse backgrounds answering the same questions, as well as sharing their compelling stories, guiding ideals, and insightful wisdom. The inimitable Ruth Bader Ginsburg, an associate justice of the US Supreme Court, embodies the power of persistence and integrity. Throughout her legal career, spanning nearly five decades, she has been an unwavering force for progress and a leading voice for equality and justice. Here, she reflects on her many years of service to the law, as well as her family life and struggle with cancer. With disarming honesty, Ginsburg discusses everything from gender equality and fitness to literature and the importance of hard work. Strong, hopeful and wise, her words stand as a guide for budding feminists and those who fight for justice around the world. Inspired by Nelson Mandela's legacy and created in collaboration with the Nelson Mandela Foundation, I Know This to Be True is a global series of books created to spark a new generation of leaders. This series offers encouragement and guidance to graduates, future leaders, and anyone hoping to make a positive impact on the world. Royalties from sales of the series support the free distribution of material from the series to the world's developing economy countries.
Includes bibliographical references.
Keywords: Ginsburg, Ruth Bader; United States. -- Supreme Court; Women judges -- United States -- Interviews; Judges -- United States -- Interviews